Associations between body mass index and the risk of renal events in patients with type 2 diabetes - Mohammedi, K; Chalmers, J; Herrington, W; Li, Q; Mancia, G; Marre, M; Poulter, N; Rodgers, A; Williams, B; Perkovic, V; Coresh, J; Woodward, M (Nature Publishing Group, 2018)
Background/Objectives: We aimed to evaluate the relationship between BMI and the risk of renal disease in patients with type 2 diabetes in the Action in Diabetes and Vascular Disease: PreterAx and DiamicroN Modified-Release Controlled Evaluation (ADVANCE) study. Subjects/Methods: Participants were divided into 6 baseline BMI categories: <18.5 (underweight, n=58); ≥18.5 – <25 (normal, n=2894); ≥25 – <30 (overweight, n=4340); ≥30 – <35 (obesity grade 1, n=2265); ≥35 – <40 (obesity grade 2, n=744); and ≥40 kg/m2 (obesity grade 3, n=294); those underweight were excluded. The composite outcome “major renal event” was defined as development of new macroalbuminuria, doubling of creatinine, end stage renal disease, or renal death. These outcomes and development of new microalbuminuria were considered individually as secondary endpoints. Results: During 5-years of follow-up, major renal events occurred in 487 (4.6%) patients. The risk increased with higher BMI. Multivariable-adjusted HRs (95%CIs), compared to normal weight, were: 0.91 (0.72 – 1.15) for overweight; 1.03 (0.77 – 1.37) for obesity grade 1; 1.42 (0.98 – 2.07) for grade 2; and 2.16 (1.34 – 3.48) for grade 3 (p for trend=0.006). These findings were similar across subgroups by randomized interventions (intensive versus standard glucose control and perindopril-indapamide versus placebo). Every additional unit of BMI over 25 kg/m2 increased the risk of major renal events by 4 (1 – 6)%. Comparable results were observed with the risk of secondary endpoints. Conclusions: Higher BMI is an independent predictor of major renal events in patients with type 2 diabetes. Our findings encourage weight loss to improve nephroprotection in these patients.